Relative compatibility of Schistosoma mansoni with Biomphalaria sudanica and B. pfeifferi from Kenya as assessed by PCR amplification of the S. mansoni ND5 gene in conjunction with traditional methods. Issue 1 (December 2016) - Lu, Lijun; Zhang, Si-Ming; Mutuku, Martin; Mkoji, Gerald; Loker, Eric
Abstract Background Schistosoma mansoni is hosted by several species ofBiomphalaria spp. snails in Africa. We were interested in determining if there were differences in compatibility ofS. mansoni withBiomphalaria sudanica from Lake Victoria, or withB. pfeifferi from streams and smaller water bodies in Kenya. Does this parasite develop with equal efficiency in both snail species, and does this have implications for transmission in different habitat types? Methods Primers for PCR amplification of theS. mansoni ND5 gene were designed and tested for sensitivity and specificity. We exposed laboratory-rearedB. sudanica and field-derivedB. pfeifferi to single miracidium infections and at 1, 2, 4, 8, 16 and 24 days post-exposure (dpe), snails were extracted for the PCR assay. Snails were also shed for cercariae and/or dissected prior to extraction. Additionally, B. sudanica andB. pfeifferi were collected from field locations and tested with the PCR assay. Results TheND5 PCR assay was sensitive (>0.1 fg S. mansoni genomic DNA) and allowedS. mansoni to be differentiated from other relevant schistosome species or snails. The number of PCR positive snails at 1–4 dpe was higher forB. pfeifferi than forB. sudanica, but not significantly so (P  = 0.052). From 8–24 dpe, moreB. pfeifferi harbored successfully developing parasites (positive by both dissection and PCR) than didB. sudanica (P  = 0.008). At 40 dpe, moreB. pfeifferi thanB. sudanica shed cercariae or harbored dissection positive/PCR positive infections (P  < 0.001). Both immature and failed (dissection negative but PCR positive)S. mansoni infections could also be detected in naturally infected snails of both species. Conclusions The PCR assay detectedS. mansoni infections in snails exposed to one miracidium for one day. BothB. sudanica andB. pfeifferi supported full development ofS. mansoni, butB. pfeifferi was more compatible, with significantly more dissection positive/PCR positive or shedding infections, and significantly fewer failed infections (dissection negative/PCR positive). This highlights the relatively lower compatibility ofB. sudanica withS. mansoni, and suggests the factors responsible for incompatibility and how they might affect transmission ofS. mansoni in habitats like Lake Victoria deserve additional study.